Indian guidelines for indications and timing of intervention for common congenital heart diseases: Revised and updated consensus statement of the Working group on management of congenital heart diseases - Anita Saxena; Jay Relan; Ravi Agarwal; Neeraj Awasthy; Sushil Azad; Manisha Chakrabarty; Kulbhushan S Dagar; Velayoudam Devagourou; Baiju S Dharan; Saurabh K Gupta; Krishna S Iyer; M Jayranganath; et al. (Wolters Kluwer Medknow Publications, 2019)
A number of guidelines are available for the management of congenital heart diseases (CHD) from infancy to adult life. However, these guidelines are for patients living in high-income countries. Separate guidelines, applicable to Indian children, are required when recommending an intervention for CHD, as often these patients present late in the course of the disease and may have coexisting morbidities and malnutrition. Guidelines emerged following expert deliberations at the National Consensus Meeting on Management of Congenital Heart Diseases in India, held on August 10 and 11, 2018, at the All India Institute of Medical Sciences. The meeting was supported by Children's HeartLink, a nongovernmental organization based in Minnesota, USA. The aim of the study was to frame evidence-based guidelines for (i) indications and optimal timing of intervention in common CHD; (ii) follow-up protocols for patients who have undergone cardiac surgery/catheter interventions for CHD; and (iii) indications for use of pacemakers in children. Evidence-based recommendations are provided for indications and timing of intervention in common CHD, including left-to-right shunts (atrial septal defect, ventricular septal defect, atrioventricular septal defect, patent ductus arteriosus, and others), obstructive lesions (pulmonary stenosis, aortic stenosis, and coarctation of aorta), and cyanotic CHD (tetralogy of Fallot, transposition of great arteries, univentricular hearts, total anomalous pulmonary venous connection, Ebstein's anomaly, and others). In addition, protocols for follow-up of postsurgical patients are also described, disease wise. Guidelines are also given on indications for implantation of permanent pacemakers in children.